Persepsi Penggunaan Sistem E-learning menggunakan Technology Acceptance Model (TAM) - Deasylia Aryanti; Joy Nashar Utamajaya (STMIK Budi Darma, 2022)
E-learning is a learning activity that uses the internet which can be combined with face-to-face activities in educational institutions. Utilization of e-learning can also make the development of high learning flexibility. The user's perception in this case is that students will be needed to help optimally use e-learning. STMIK Borneo International Balikpapan is one of the educational institutions that has developed an e-learning system. This study aims to examine student behavior in the use of e-learning STMIK Borneo International Balikpapan on the e-learning system with the Technology Acceptance Model (TAM) using SPSS version 26 as data processing with the aim of providing convenience and acceleration in the research completion process. Respondents in this study were 37 students in 2018. The data collection method used an electronic questionnaire (google form), a measuring instrument with a Likert scale, in validity and reliability tests and descriptive analysis by looking for the average value of each question item. The research model uses the Technology Acceptance Model (TAM) with 3 variables, namely user acceptance (Acceptance), ease of use (Ease of Use), and usefulness (Usefulness). The results of the analysis show that the perception of the use of the e-learning system is the average overall value of the mean score usefulness (Usefulness) 4, ease (Ease of Use) 3.6, acceptance (Acceptance) 4.03. So it can be concluded that respondents get good benefits in using the e-learning system